Global Green System of Innovation: Technological Wave or Policy? - Marinova, Dora (The Modelling and Simulation Society of Australia and New Zealand, 2009)
In the tradition of technological innovation waves (modelled following Kondratieff’s long waves hypothesis), the paper explores the emergence of the 6th technological wave associated with the development of new technological classes, such as renewable energy and nanotechnology. Based on 1975-2007 data from the US Patent and Trademark Office (USPTO), it analyses the emerging patterns in these two classes of sustainable technologies. The surge in activities related to nanotechnologies is in contrast with a much lower interest in inventions related to renewable energy technologies. The paper argues that left on the national and sectoral innovation systems existing around the world, it is unlikely to see a fast uptake of technologies that help mitigate or adapt to the imperatives of climate. On the other hand, the scientific evidence on the impact of CO2 on the earth’s atmosphere calls for immediate actions and would not allow enough time for the global community to ride the 6th technological wave. Urgent policy measures are needed to speed up the process of technology development and as distinct to any other period in the history of technology development, these actions need to be taken at a global scale. The paper puts forward the need for a global green system of innovation (GGSI) that represents community values and encourages sustainable behaviour.